2015
DOI: 10.1073/pnas.1511904112
|View full text |Cite
|
Sign up to set email alerts
|

Extent of hippocampal atrophy predicts degree of deficit in recall

Abstract: Which specific memory functions are dependent on the hippocampus is still debated. The availability of a large cohort of patients who had sustained relatively selective hippocampal damage early in life enabled us to determine which type of mnemonic deficit showed a correlation with extent of hippocampal injury. We assessed our patient cohort on a test that provides measures of recognition and recall that are equated for difficulty and found that the patients' performance on the recall tests correlated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Indeed, we found that hippocampal GMV made a unique, positive contribution to the M1 factor. This is consistent with the hypothesized role of hippocampus in associative memory24, despite mixed findings in prior attempts to associate memory scores with structural brain measures606162 (though see refs 63 and 64). However, any simple dependence of M2 on anterior parahippocampus (as expected from prior association of perirhinal cortex with familiarity65), was not supported; nor was any simple dependence of M3 on fusiform (as expected from prior association of this region with visual priming66).…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, we found that hippocampal GMV made a unique, positive contribution to the M1 factor. This is consistent with the hypothesized role of hippocampus in associative memory24, despite mixed findings in prior attempts to associate memory scores with structural brain measures606162 (though see refs 63 and 64). However, any simple dependence of M2 on anterior parahippocampus (as expected from prior association of perirhinal cortex with familiarity65), was not supported; nor was any simple dependence of M3 on fusiform (as expected from prior association of this region with visual priming66).…”
Section: Discussionsupporting
confidence: 83%
“…Whereas we failed to find a correlation between hippocampal volumes and the patients' memory performance in the current study, we had previously shown that such a relationship exists in a larger sample of patients with a history of neonatal hypoxia-ischaemia, whose hippocampal volumes ranged from severely reduced to normal (Cooper et al., 2015; see also; Patai et al., 2015). These results are not necessarily inconsistent.…”
Section: Discussionmentioning
confidence: 90%
“…Volumetric measurements of the hippocampus were carried out by one of the authors (DGG) (Gadian et al., 2000, Patai et al., 2015) using MEDx 3.43 (Medical Numerics, Inc., MD, USA). Detailed information on the procedures that were used for pre-processing of images, including identifying and outlining the boundaries of the hippocampus, is contained in Cooper et al.…”
Section: Methodsmentioning
confidence: 99%
“…Recall refers to the ability to bring back to mind consolidated representations and relies on recollection processes. Based on evidence from patients with bilateral hippocampal damage of early onset, it is recognized that the hippocampus supports recall processes (56). Recall-based memory should be considered in memory fMRI studies to represent ecological scenarios of everyday memory process, and to optimize hippocampal activation.…”
Section: Recallmentioning
confidence: 99%